Legal Governance for Extreme Poverty Reduction: Advancing Justice through Participatory Public Policy - M. Yulian Akbar; Teguh Yuwono; Bangkit Aditya Wiryawan; Hardi Warsono (Unissula, 2026)
This study examines extreme poverty alleviation in Pekalongan Regency from a legal governance perspective by integrating normative and empirical analyses. It addresses the gap between Indonesia’s comprehensive legal framework and its implementation at the local level. Using a normative empirical juridical approach, the study analyzes the 1945 Constitution, Law Number 25 of 2004, Law Number 23 of 2014 as amended by Law Number 6 of 2023, Presidential Regulation Number 15 of 2010, and Presidential Instruction Number 4 of 2022, alongside their implementation in poverty reduction policies. The findings show that Indonesia has a strong normative foundation for poverty alleviation through social protection programs, including PKH, JKN, PIP, food assistance, and Village Funds. However, implementation remains dominated by an administrative approach, while justice, accountability, transparency, and public participation have not been fully institutionalized. The Pekalongan case reveals persistent problems, including inaccurate beneficiary data, institutional fragmentation, limited transparency, and weak public participation. The study concludes that strengthening legal governance through integrated welfare data, outcome-based accountability, digital transparency, and meaningful community participation is essential for achieving more just, effective, and sustainable extreme poverty alleviation.